Management of production waste and garbage, their collection and disposal in catering establishments - Kuzmenko, Rostislav; Maksymiuk, Anna; Fefelov, Denys; Omelchenko, Mariia; Kuzmin, Oleg (My University, 2024)
Дослідження розглядає ефективні методи і стратегії управління виробничими відходами у закладах громадського харчування для зменшення екологічного впливу та підтримки стійкого розвитку

The study explores effective methods and strategies for managing production waste in catering establishments to minimize environmental impact and promote sustainability
Keywords: кафедра технології ресторанної і аюрведичної продукції; управління відходами; заклади громадського харчування; харчові відходи; переробка; екологічна стійкість; waste management; catering establishments; food waste; recycling; environmental sustainability